Annular epidermolytic ichthyosis: a case report and literature review, - Emanuella Stella Mikilita; Irina Paipilla Hernandez; Ana Letícia Boff; Ana Elisa Kiszewski (Sociedade Brasileira de Dermatologia, 2020)
Abstract Annular epidermolytic ichthyosis is a rare subtype of epidermolytic ichthyosis that is characterized by erythematous, polycyclic, and migratory scaly plaques accompanied by palmoplantar keratoderma. This report presents the case of an 8-year-old girl who developed migratory, erythematous, scaly plaques associated with palmoplantar keratoderma. The initial hypothesis was erythrokeratodermia variabilis et progressiva; however, the finding of epidermolytic hyperkeratosis in histopathological examination led to the diagnosis of annular epidermolytic ichthyosis.